Tingkat Motivasi Belajar Mahasiswa Pada Mata Kuliah Difusi Inovasi Pendidikan Dengan Menggunakan SPADA - Nurindah (Jurnal Pendidikan dan Pembelajaran, 2022)
The level of student learning motivation in the diffusion course of educational innovation by using an online learning system in the Educational Technology study program at the University of Muhammadiyah Makassar. The purpose of this study was to determine the amount of student motivation in learning using SPADA. The method used in this study is a descriptive research method, which describes the results of the research carried out. Respondents were students in the odd semester who programmed the Educational Innovation Diffusion course as many as 30 students. The data collection technique used in this study used questionnaires (questionnaires) and documentation. The data is processed with descriptive techniques. The results of the study data show that the level of student learning motivation is classified as a very high category which is expected to be directly proportional to student learning outcomes using SPADA.